Paulus Dan Moderasi Beragama: Membangun Keselarasan Dalam Kehidupan Iman - Darmiati Lamba; Rida Ari (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This article explores the Apostle Paul's views on religious moderation as the key to building harmony in the faith life of the Christian community. Through analysis of Paul's letters, this study discusses the main concepts proposed by Paul, including unity in diversity, attitudes of love, forgiveness, and inclusiveness. The focus of the study is on Paul's efforts to form a theological and practical foundation for Christians to be able to live in harmony, understand differences, and establish inclusive relationships. This study also explores how Paul's views remain relevant in the context of diversity and social challenges faced by Christians in the modern era.